2011
DOI: 10.1071/bt10312
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the polyploid complex Cenchrus ciliaris L. (Poaceae) show its capacity for gene flow and recombination processes despite its apomictic nature

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
3
17
2
Order By: Relevance
“…In these studies the phenotypic variables measured showed considerable differences among populations of C. ciliaris and among maternal parent plants within the same population (Kharrat-Souissi et al 2011). This was a novel result compared with previous studies on the morphological variability of C. ciliaris.…”
Section: Intra-specific Phenotypic Variationmentioning
confidence: 93%
See 4 more Smart Citations
“…In these studies the phenotypic variables measured showed considerable differences among populations of C. ciliaris and among maternal parent plants within the same population (Kharrat-Souissi et al 2011). This was a novel result compared with previous studies on the morphological variability of C. ciliaris.…”
Section: Intra-specific Phenotypic Variationmentioning
confidence: 93%
“…Considering the ecological interest offered by C. ciliaris: drought tolerance (Bhatt et al 2007; De La Barrera and Castellanos 2007;Kharrat-Souissi et al 2012a), high fodder production and nutritive value to livestock (Kharrat-Souissi et al 2010;Arshadullah et al 2011), rapid regeneration in response to rainfall (Bose and Balakarishnan 2001), tolerance of heavy grazing (M'seddi et al 2004a) and soil stabilisation abilities because of a deep root system (Chaieb et al 1996;Mnif and Chaieb 2009), the persistence of this species in its native range in arid ecosystems is a crucial factor for restoration ecology of degraded arid rangelands. For these reasons, C. ciliaris has been the subject of numerous applied studies, which have focussed on its phenotypic polymorphism, its ecological significance (M'seddi et al 2002;Arshad et al 2007;Jorge et al 2008;Visser et al 2008;Kharrat-Souissi et al 2010;Arshadullah et al 2011), resistance to drought (Mansoor et al 2002;Mnif and Chaieb 2010;Kharrat-Souissi et al 2012a), biological invasion capacity (Friedel et al 1996;Franklin et al 2006;GutierrezOzuna et al 2009;Marshall et al 2012) and its genotypic diversity (Nisar et al 2010;Al-Soqeer 2011;Kharrat-Souissi et al 2011).…”
Section: Adaptive Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations